On the least trimmed squares estimators for JS circular regression model - Alshiqaq, Shokrya Saleh (Kuwait Journal of Science, 2021)
The least trimmed squares (LT S) estimation has been successfully used in the robust linear regression models. This paper, extends the LT S estimation to the JS circular regression model. The robustness of the proposed estimator is studied and discuss the algorithm for computation. Simulation studies and real data show that the proposed robust circular estimator is effective in fitting JS circular models in the presence of vertical outliers and leverage points.